2014
DOI: 10.4067/s0717-95532014000300006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación Del Efecto a Largo Plazo De Intervenciones Educativas Para El Autocuidado De La Diabetes

Abstract: RESUMENObjetivo: Analizar la evidencia respecto a la evaluación del efecto a largo plazo de intervenciones educativas para el autocuidado de la diabetes. Material y método: Búsqueda de artículos científicos introduciendo las palabras clave en las bases de datos EBSCO, PUBMED y buscador Google Académico. Se seleccionaron y revisaron artículos publicados desde enero 2001 hasta diciembre 2012. Resultados: Fueron seleccionadas y analizadas ocho intervenciones dirigidas a personas con Diabetes Mellitus Tipo 2 (DMT2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In the model used for the intervention, the follow-up stage of the participants is distinguished. Some authors have reported significant results from the follow-up of people in educational interventions (Pimentel et al, 2014) [59]. Follow-ups focused on motivation and accompaniment, as well as providing constant and adequate information according to the doubts that arise help people to generate security and better results (García and Suárez, 2003) [60].…”
Section: Economic Aspects Of Food Dishesmentioning
confidence: 99%
“…In the model used for the intervention, the follow-up stage of the participants is distinguished. Some authors have reported significant results from the follow-up of people in educational interventions (Pimentel et al, 2014) [59]. Follow-ups focused on motivation and accompaniment, as well as providing constant and adequate information according to the doubts that arise help people to generate security and better results (García and Suárez, 2003) [60].…”
Section: Economic Aspects Of Food Dishesmentioning
confidence: 99%
“…Globally, the prevalence of diabetes keeps growing [3][4][5] ; more than 382 million individuals in the world suffer from this disease today and this number is expected to increases to 592 million by 2035 [6][7][8][9] , being higher in developing countries like Colombia [10][11] .…”
Section: Introductionmentioning
confidence: 99%